Tele-revista y la Transición : un programa de la televisión suiza para emigrantes españoles (1973-1989) - Calvo Salgado, Luis M.; Langa Nuño, Concha; Prieto Lopez, Moises (Iberoamericana, 2015)
Tele-revista, a Swiss TV news program, was broadcasted in Spanish for Spanish emigrants living in Switzerland.